Cardiac effects of volatile agents - Vural, Mutlu; Ögel, Kültegin (Journal of Dependence, 2005)
It is known that volatile agents have negative effects on the heart as well as other body organs. These cardiac side effects could be sudden death due to ventricular tachyarrhythmia, heart failure and myocardial infarction. Apart from industrial exposure, volatile agent exposure occurs to a significant extent by abusing these substances with the aim of excitement. Despite widespread exposure to volatile substances in our country, the scarcity of published data on cardiac effects of these substances is a contradiction. It is stated that, these negative effects are largely overlooked.